Welcome to Ecuador - Alexander, Vimala; Daniels, Amy S. (Wisconsin : Gareth Stevens, 2003)
An overview of the geography, history, government, economy, people, and culture of Ecuador.
Includes glossary and index
Includes bibliographical references
Primary
Keywords: Ecuador